KAJIAN PORTAL BAJA SRPMB (ELASTIS) DAN PORTAL BAJA SRPMK (DAKTAIL) BERDASARKAN SNI 03-1726-2012 DAN SNI 03-1729-2002 - Hamdany Auliya; Sarwiasih Tri Purboningrum; Han Ay Lie; Himawan Indarto (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
The most current Indonesia National Standard on earthquakes SNI 03-1726-2012 is designed to anticipate the latest earthquake events in the past decade. This standard as well as the former SNI 03-1729-2002 incorporates the guidance for Ordinary Moment Resisting Frame Systems(SRPMB)andSpecial Moment Resisting Frame Systems (SRPMK). This study evaluates the performance steel frames based on the two standards for high, and intermediate seismic regions with a variation in soil conditions. The aim of this study was to obtain the most appropriate structural steel system for high and intermediate earthquake regions. The analysis was performed with the aid of a structural analysis program, and approached as a two-dimensional case. The responseof earthquake loads was analyzed by the dynamic response spectrum modal analysis on 8, 10 and 12 storey buildings. The Semarang area was chosen for the intermediate seismic response, while Banda Aceh functioned a prototype for the high seismic area. Three soil types were taken into consideration; hard, medium and soft soil. The study showed that the nominal of the earthquake load in the area of Banda Aceh was approximately equal to 164% of the nominal earthquake load in Semarang. For the variations in soil type it was found that for the Semarang as well as the Banda Aceh region, the nominal earthquake loads on a steel structure based on the SRPMB was approximately equal to 228,6% to the SRPMK. Further it was concluded that the SRPMK steel stucture was able to reduce the earthquake load by approximately 87,5% as compared to the SRPMB steel structure that resulted in an earthquake load reduction of 71,4%. It was therefore advised to use the SRPMK in designing steel structures for areas in high seismic regions, whiles for the medium seismic regions the both the SRPMB and the SRPMK method will yield in an optimum design.